2019
DOI: 10.1007/s11069-019-03643-y
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of dike breaches and dike overflow in a bifurcating river system

Abstract: Currently, the effect of dike breaches on downstream discharge partitioning and flood risk is not addressed in flood safety assessments. In a bifurcating river system, a dike breach may cause overland flows which can change downstream flood risk and discharge partitioning. This study examines how dike breaches and overflow affect overland flow patterns and discharges of the rivers of the Rhine delta. For extreme discharges, an increase in flood risk along the river branch with the smallest discharge capacity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 27 publications
0
56
0
1
Order By: Relevance
“…If the simulated water levels in the 1D proles exceed the dike crest levels, water starts to ow into the storage areas corresponding with inundations of the hinterland. Bomers et al (2019b) showed that for the discharge range considered in this study, no signicant overland ows are present. The water that leaves the river system is not capable of owing back into the river at a downstream location.…”
Section: Reconstruction Of the 1809 Geometrymentioning
confidence: 63%
See 1 more Smart Citation
“…If the simulated water levels in the 1D proles exceed the dike crest levels, water starts to ow into the storage areas corresponding with inundations of the hinterland. Bomers et al (2019b) showed that for the discharge range considered in this study, no signicant overland ows are present. The water that leaves the river system is not capable of owing back into the river at a downstream location.…”
Section: Reconstruction Of the 1809 Geometrymentioning
confidence: 63%
“…This is because a low discharge with a high main channel friction results in a similar simulated water level as a high discharge with a low main channel friction. Therefore, a 1D-2D coupled model calibrated with the 1995 ood event, available from previous work (Bomers et al, 2019b), is used to determine the friction range used. The range is set equal to the minimum and maximum Manning's friction values found after calibration.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Consequently, it might be that the discharge wave shape used as boundary condition is not correct since this has a typical shape of a normal flood event generated by a precipitation event. However, the work of Bomers et al (2019d) shows that the discharge wave shape only has a little effect on downstream maximum discharges. Hence, the reconstructed discharge at Lobith represents a reliable maximum number.…”
Section: The Effects Of Ice Jams On Model Resultsmentioning
confidence: 99%
“…This is because a low discharge with a high main channel friction results in a similar simulated water level as a high discharge with a low main channel friction. Therefore, a 1-D/2-D coupled model calibrated with the 1995 flood event, available from previous work (Bomers et al, 2019d), is used to determine the friction range used. The range is set equal to the minimum and maximum Manning's friction values found after calibration.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Since the 1374 flood event was much larger than the current discharge capacity of the Lower Rhine, the maximum discharge at Lobith decreases. The reconstruction of the 1374 flood over modern topography is presented in detail in Bomers et al (2019b). On the other hand, the other 11 flood events were below this discharge capacity and hence only a slight reduction in discharges was found for some of the events as a result of dike breaches, whereas overflow did not occur.…”
Section: Normalization Of the Historic Flood Eventsmentioning
confidence: 99%